Quality characteristics and storage stability of low-fat tofu prepared with defatted soy flours treated by supercritical-CO2 and hexane. (February 2019) - Lee, Kyo-Yeon; Rahman, M. Shafiur; Kim, Ah-Na; Gul, Khalid; Kang, Sung-Won; Chun, Jiyeon; Kerr, William L.; Choi, Sung-Gil
Abstract: The objective of this study was to test the yield and quality of low-fat tofu (LFT) using defatted soy flour (DF) treated by supercritical-CO2 (SC-CO2 ) and hexane. Characteristics such as yield, textural attributes, color values, microstructure and storage stability of LFTs were measured and compared. SDS-PAGE showed that DF-SC had no protein denaturation, while DF-H had substantial denaturation. DF using SC-CO2 (DF–SC) had higher soluble solids (51.89 g/100 g) in soy milk than in the control (40.58 g/100 g) or that treated by hexane (DF–H, 23.10 g/100 g). DF–SC resulted in remarkably higher tofu yield (g/100 g soy flour) with values of 535.47, followed by 385.23 for the control, and 351.23 for DF–H. Tofu made from DF-SC had a softer texture than the other tofus, likely due to the relatively high moisture content. SEM images showed that tofu from DF-SC had uniform and homogenous microstructure with a dense protein network. The DF-SC tofu also had higher oxidative and microbiological stability than the control and hexane–treated tofu. SC-CO2 treatment results in higher tofu yield with a softer texture and homogenous microstructure, increased shelf-life and with significant reduction of microbial contamination. Highlights: Low-fat tofu using SC-CO2 and hexane-treated soy flours were prepared and compared. SC-CO2 –treated soy flour resulted in higher soluble solids and higher tofu yield. SDS-PAGE showed no protein denaturation in SC-CO2 –treated soy flour. SC-CO2 –treated tofu had a softer texture and homogenous microstructure. Lower microbial counts were observed in SC-CO2 –treated tofu during storage.